2022
DOI: 10.3390/ma15062231
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Vertical Ductility of Rectangular CFST Columns Loaded Axially

Abstract: A total of 5 steel and 21 rectangular composite concrete-filled steel tube (CFST) columns of moderate slenderness were tested to investigate their ductility under axial compression. The importance of the vertical ductility of columns was discussed, and a novel ductility measure was proposed and utilized to examine the ductility of tested specimens. The analyses showed that the ductility of axially compressed CFST columns highly depends on their failure mode. The key feature influencing the ductility is their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, the bending stiffness in the corner was large, and the deformation was small. Under the action of mutually perpendicular tension, strong constraints were formed on the core concrete along the diagonal direction [15,16]. At the same time, the above test phenomena revealed that the local bulge deformation of the specimen occurred mainly on the outside of the shaped steel tube.…”
Section: Bearing Mechanismmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the bending stiffness in the corner was large, and the deformation was small. Under the action of mutually perpendicular tension, strong constraints were formed on the core concrete along the diagonal direction [15,16]. At the same time, the above test phenomena revealed that the local bulge deformation of the specimen occurred mainly on the outside of the shaped steel tube.…”
Section: Bearing Mechanismmentioning
confidence: 84%
“…However, the bending stiffness in the corner was large, and the deformation was small. Under the action of mutually perpendicular tension, strong constraints were formed on the core concrete along the diagonal direction [15,16]. Core concrete can be divided into effectively confined and ineffectively confined areas due to stirrups' restraint effects on core concrete.…”
Section: Bearing Mechanismmentioning
confidence: 99%
“…At the present time, many numerical and experimental works (Alatshan et al [4], Chepurnenko et al [5], Grzeszykowski and Szmigiera [6], Florence and Senthil [7], Zhen et al [8]) are devoted to the topic of columns having hollow profiles filled with concrete. Storozhenko et al [9] performed experiments on high-strength composite columns subjected to eccentric loading.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete-filled steel tube (CFST) columns have been widely used in heavy-duty structures or underground structures in recent decades, such as high-speed railway passenger stations, subways, and other underground structures [ 1 , 2 , 3 ]. The composition effect between the steel tube and infilled concrete in CFST columns enhances the axial strength and deformation performances.…”
Section: Introductionmentioning
confidence: 99%